Detection of Spoilage in Canned Pasteurized Milk Using the Radiographic Imaging Technique - D. T. Thuy; H. B. Tien; H. B. Ngoc; T. T. Kim; T. T. Ngoc (PPIKSN-BATAN, 2022)
After packed into sterilized containers with a closed and rigorous process, pasteurized milk has been ensured for its hygiene and safety factors. However, distortions can occur during storage and transportation, causing the container to open, allowing harmful microorganisms to enter and damage the product. This research proposed a radiographic imaging technique to detect and evaluate the spoilage of canned pasteurized milk. The X-ray images show that the milk cans, which were left open for three days at 300 K, indicated regions with abnormal density with the smallest detectable size from 100 µm or larger. Density heterogeneity would be clearer in the following days and depending on the sample. An algorithm was developed to identify spoilage products automatically with an accuracy of up to 100 % and a speed of 0.0057 s/product. This approach may be suitable for industrial scale to control the quality of dairy products.